THERMAL WORK OF PROLONGED ELECTRICAL FURNACES AT HEATING OF STEEL WIRE UNDER THERMAL TREATMENT - Usenko , Yuri; Ivanov , Victor; Cheprasov , Alexander; Zinchenko , Yuri; Kayukov , Yuri; Poleshko , Yuri (Scientific Journal "Metallurgy", 2020)
The results of development of algorithm for analytical research of heating of steel wire under heat treatment in prolonged elecrtofurnaces before the hot zinc-plating are presented. Measures are worked out on the rational redistribution of thermal power of stoves after length of the swept volume, and also decline to a minimum of losses of warmth through a vault and lateral walls of second and third areas. Practice of exploitation of prolonged elecrtofurnaces showed before the hot zincking of steel wire, that during their work the considerable expense of electric power and substantial losses of warmth by a radiation through a vault and lateral walls of second and third areas of the swept volume are fixed. During development of the energysaving mode of heating of steel wire under heat treatment in prolonged elecrtofurnaces. Authors used the algorithm of analytical research, which contains procedure of search of rational temperature condition which provides the receipt of metal with the analogical indexes of quality at more subzero specific expense of electric power. To basis of algorithm equation of heating thermally of thin body is fixed on radiation heat exchange on an external surface with the coefficients of heat emission, which depend on the temperature of the swept volume of furnace and surfaces of metal, which heat. Such algorithm will realize the known principle of economic control prolonged elecrtofurnaces that foresees intensification of heating of metal in areas, last on motion of its transporting, for providing of minimum power charges on its realization. As a criterion authentications authors accepted the maximal rejection of calculation and experimental values of temperature of wire in the areas of furnace, the value of which must not exceed 2,0 % measured for the mode, that it is foreseen by technological instruction. It is set that the maximal rejection of temperature for different speed of transporting of wire did not exceed a set value, id est adequacy of the offered model is fixed to the real process. Results of calculations is set, that the value of decline of expense of elecrtofurnaces after realization of the corrected mode of heating of wire under heat treatment answers the decline of expense of electric power in elecrtofurnaces